Fetal thoraco-abdominal lymphangioma: a case report - Ghazal, Kariman; Rajab, Mariam; Malas, Abir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Lymphangiomas are rare congenital malformations of the lymphatic system. Authors present a case with giant, septated, axillary thoraco-abdominal lymphangioma. Diagnosis was made at 19 weeks’ gestation by antenatal ultrasonography. The case underwent prenatal expectation treatment.